2016
DOI: 10.1111/bjh.14101
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy with pixantrone in histologically confirmed relapsed or refractory aggressive B‐cell non‐Hodgkin lymphoma: post‐hoc analyses from a phase III trial

Abstract: This post hoc analysis of a phase 3 trial explored the effect of pixantrone in patients (50 pixantrone, 47 comparator) with relapsed or refractory aggressive B‐cell non‐Hodgkin lymphoma (NHL) confirmed by centralized histological review. Patients received 28‐d cycles of 85 mg/m2 pixantrone dimaleate (equivalent to 50 mg/m2 in the approved formulation) on days 1, 8 and 15, or comparator. The population was subdivided according to previous rituximab use and whether they received the study treatment as 3rd or 4th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…9 Subsequent post hoc analyses of this study confirmed that pixantrone was more effective than comparator agents in patients with relapsed or refractory aggressive B-cell NHL in third-or fourth-line settings, independently of previous rituximab therapy. 10 The first real-world data on pixantrone were published in 2016; a UK-based retrospective study has suggested that patients who relapse >12 months after first-line treatment, those with fewer prior lines of therapy, and relapsed (non-refractory) DLBCL gain greater benefit from pixantrone compared with patients who relapse earlier, have had more lines of prior therapy, or have refractory DLBCL. 11 Despite this evidence, data on the use of pixantrone in everyday clinical practice remain scarce.…”
mentioning
confidence: 99%
“…9 Subsequent post hoc analyses of this study confirmed that pixantrone was more effective than comparator agents in patients with relapsed or refractory aggressive B-cell NHL in third-or fourth-line settings, independently of previous rituximab therapy. 10 The first real-world data on pixantrone were published in 2016; a UK-based retrospective study has suggested that patients who relapse >12 months after first-line treatment, those with fewer prior lines of therapy, and relapsed (non-refractory) DLBCL gain greater benefit from pixantrone compared with patients who relapse earlier, have had more lines of prior therapy, or have refractory DLBCL. 11 Despite this evidence, data on the use of pixantrone in everyday clinical practice remain scarce.…”
mentioning
confidence: 99%
“…Pixantrone monotherapy is approved in Europe in patients with multiply relapsed/refractory aggressive NHL (European Medicines Agency, ). In its pivotal phase 3 trial (PIX301), pixantrone was associated with significantly higher complete response (CR; 20·0% vs. 5·7%) and longer progression‐free survival (PFS; median 5·3 vs. 2·6 months) than comparator in multiply relapsed/refractory aggressive NHL (Pettengell et al , ; Pettengell et al , ). However, at the time when the PIX301 study was conducted, rituximab had not yet become standard treatment for NHL and only 54% of included patients received it before study entry (Pettengell et al , ).…”
mentioning
confidence: 99%
“…To address these concerns, post hoc subgroup analyses of the phase III trial were conducted, which confirmed the superior efficacy of pixantrone as a salvage therapy. Among 97 patients with aggressive B-cell lymphoma (DLBCL, transformed indolent lymphoma and follicular lymphoma, grade 3 confirmed by blinded centralized review) who were receiving study drug as their third or fourth line of therapy had an ORR of 43.6% versus 12.8% (p = 0.005) and a CR/CRu of 23.1% vs. 5.1% (p = 0.047) for pixantrone versus the comparator agent group [37]. Within this subgroup, analysis of those who had previously received rituximab indicated that treatment with pixantrone was associated with a better response than comparator drug (ORR 45% vs. 11.1%; p = 0.033) [37].…”
Section: Cardiac Effectsmentioning
confidence: 99%